Code name Banshee [videorecording (DVD)] - Rogers, Matthew; Banderas, Antonio; King, Jaime, 1979-; Flanagan, Tommy, 1965- (Screen Media, 2022)
A former government assassin is forced out of hiding when his deadly protǧ ̌known as Banshee discovers there is a bounty on his life. To survive, they must fight off the CIA backed killers coming for them.